2004
DOI: 10.1293/tox.17.261
|View full text |Cite
|
Sign up to set email alerts
|

Absence of &beta;<i>-catenin</i> Mutations in Mouse Hepatoblastomas Induced by <i>N</i>, <i>N</i>-dimethylformamide

Abstract: Abnormal β-catenin protein accumulation in cytoplasm or nucleus with somatic mutation of β-catenin has been reported to be very frequent in hepatoblastomas (HBs) both in humans and in experimental animals. Recently we noted HBs developing in an evaluation of the carcinogenicity of N, N-dimethylformamide (DMF) in a 104 week mouse inhalation study 1 performed by the Japan Bioassay Research Center. In the present study we evaluated β-catenin mutations in mouse HBs induced by DMF, which is considered to be a non-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(30 reference statements)
0
3
1
Order By: Relevance
“…There are many reports of high percentages of HBs with gene mutation and abnormal localization of β-catenin in mice (de La Coste et al, 1998; Devereux et al, 1999; Anna et al, 2000, 2003; Hayashi et al, 2003), in contrast to our previous (Kakuni et al, 2004) and present studies. The root causes are unclear, but it is likely that specificity regarding inducing compounds and strains of mice is involved.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…There are many reports of high percentages of HBs with gene mutation and abnormal localization of β-catenin in mice (de La Coste et al, 1998; Devereux et al, 1999; Anna et al, 2000, 2003; Hayashi et al, 2003), in contrast to our previous (Kakuni et al, 2004) and present studies. The root causes are unclear, but it is likely that specificity regarding inducing compounds and strains of mice is involved.…”
Section: Discussioncontrasting
confidence: 94%
“…Chemically induced hepatocellular adenomas (HCAs) and HCCs in 2 studies had mutations in exon 2 of β-catenin (Hayashi et al, 2003;Huang et al, 2003), but were lacking in another investigation (Aydinlik et al, 2001). Concerning HBs, there have been many reports of high percentages of gene mutations and abnormal localization of β-catenin (de La Coste et al, 1998;Devereux et al, 1999;Anna et al, 2000Anna et al, , 2003Hayashi et al, 2003), but we earlier found no change in N,N-Dimethylformamide-induced HBs in mice (Kakuni et al, 2004).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations